Efficacy of oral losartan in recessive dystrophic epidermolysis bullosa. - Jangid, S.; Madke, B.; Saoji, V.; Singh, A.L. (European Journal of Pediatric Dermatology, 2025)
Dystrophic epidermolysis bullosa is caused by a variation in the COL7A1 gene, which encodes type VII collagen. The severity of the disease depends on the type of genetic variant and the domain of the affected protein. We present the case of a 7-day-old infant with recessive dystrophic epidermolysis bullosa, who was treated with oral losartan and showed significant improvement.